DETERMINING BERNOULLI’S PRINCIPLES IN BASKET WEAVING OF MANOBO TRIBESMEN IN SOUTHERN PHILIPPINES (Journal of Technology and Operations Management, 2022)
The author determine the Bernoulli’s Principles behind the Indigenous Knowledge System and Practices (IKSP) of Manobo Dulangan in Sultan Kudarat and Erumanen Manuvu of Cotabato Province in their craft arts particularly in their bamboo weaving. An ethnographic research, whose main instruments are keen observation of these  two (2) major Indigenous Cultural Communities(ICC’s) mostly coming from Central Mindanao in Sultan Kudarat  and Cotabato province, through the National Culture in Indigenous People (NCIP)-Certificate of Compliance(CoCs), where randomly selected Manobo master weavers executed their masterpiece in bamboo’s weaving with archaeological concepts. The results that all fish scooping baskets of Manobos applied the mathematical concepts of Bernoulli’s Principle like Area one (A1) is larger than Area two(A2) (A1